PENGARUH KEDISIPLINAN, MOTIVASI, DAN KOMITMEN TERHADAP KINERJA PEGAWAI BIRO PEREKONOMIAN SETDA PROVINSI KALIMANTAN TIMUR - Nur Hasanah (OBOR: Oikonomia Borneo, 2019)
This study aims to examine and analyze the influence of discipline, motivation, and commitment on the performance of the employees of the Economic Bureau of the Regional Secretariat of East Kalimantan Province. This research uses quantitative research methods. The sample in this study were all 28 employees of the Bureau of the Economy. The data were collected by using a questionnaire that had been tested for validity and reliability. The data analysis technique used is multiple linear regression with the following test results: Y = 2.688 + 0.299X1 + 0.244X2 + 0.462X3 The results of this study indicate that there is a positive and significant effect on the performance of the employees of the Regional Secretariat of the Economic Bureau of East Kalimantan Province, and there is no and no significant effect on the performance of the employees of the Regional Secretariat of the Economic Bureau of the Province of East Kalimantan. Partially, work discipline has no effect and is not significant on employee performance with a ttable value of 2.063 > (more) tcount 1.639 with a significance value of 0.114 > (more) 0.05. Work motivation has a positive and significant effect on employee performance with a ttable value of 2,063 < (less) tcount of 2,145 with a significance value of 0.042 < 0.05. And work commitment has a positive and significant effect on employee performance with a ttable value of 2.063 < (less) tcount 2.913 with a significance value of 0.008 <0.05.